Gestão democrática: autonomia e participação na Escola Estadual 11 de Agosto Umarizal/RN - Dalva, Gercina (2010)
The object of analysis of this work is the implementation of the election of director in the State School August 11, situated in the city of Umarizal, State of Rio Grande do Norte, period 2005-2008. The understanding of the politics concerning the school democratization, triggered in Brazilian society in the 1990s, requires taking into consideration the changes occurring in recent decades in the national and international, which impressed significant changes in the role and functions of the state. The election of a director is part of the policy of administrative decentralization and educational reform that focuses on the democratization of the management of public education with the involvement of social actors in decisions within the educational institutions as a way to address the problems that hinder the actions management education, especially school management. To better understand this process of political democratization of school management developed our analysis seeking to answer the following questions: implementation of direct election for a director ensures democratic management in schools? What are the ramifications for the school, caused by direct election on the school autonomy and participation of the subjects in school processes? From these questions, we set as standard for analysis of democratic management in schools of two dimensions: participation and autonomy within the school. For this we take as a theoretical and methodological literature: Pateman (1992); Rousseau (2010); Bourdieu (2007), Castoriadis (1991); Macpherson (1978); Marx; Engels (2007), among others dealing with participation, autonomy, decision power and election of director, and guidelines dealing with the democratization of school management. As data collection procedure, we use the semi-structured interviews and analysis of meeting minutes of the School Council and the Minutes of the final results of elections, to understand the empirical aspects of the implementation of the election of a director. The survey results indicate some progress and setbacks regarding the participation of subjects from issues relating to the school's educational project. Also underline the political interference as a factor crystallizer the centralization of power in the figure of the director as well as the advancement of the spaces that nurture the mobilization of political debate on the democratization of management. About the extent of autonomy observed that social actors to relate predominantly to the power of decision and the involvement of subjects in the school's actions